Using nature’s inventions - Bar-Cohen, Yoseph (Ökologisches Wirtschaften - Fachzeitschrift, 2007)
Nature is full of inventions that work and last. Biomimetics try to imitate and use nature’s inventions. Some of the commercial implementations of biomimetics can be seen in toys. But the ultimate challenge to these efforts is the development of humanlike robots that appear and behave like living humans.